PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, KUALITAS AUDIT, AUDIT TENUR TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BEI) - Sososutiksno, Christina; Latuamury, Jabida; Risakotta, Kathleen Asyera; Sapulette, Shella Gilby; Radjawane, Erik P (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine the influence of profitabilty, company size, audit quality, and audit tenure on audit delay ini state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange (BEI) during the 2020-2023 period. Audit delay is critical concern as it affects the credibility and public trust in financial statements. Using a quantitative approach with multiple linear regression analysis, this research analyzes secondary data from 52 purposiively selected observations. The results show that company size has a significant negative effect on audit delay, while profitability, audit quality, and audit tenure do not have a significant effect. These finding provide valuable insight for BUMN companies, auditors, and regulators in understanding the factors that influence audit duration.